Dichloridobis[2-(morpholin-4-yl)ethanamine-kappa]2N,N']cadmium - Gwaram, N.S.; Khaledi, H.; Ali, Hapipah Mohd (International Union of Crystallography, 2011)
In the title compound, [CdCl2(C6H14N2O)(2)], the Cl and Cd-II atoms are located on a twofold rotation axis and the CdII atom is octahedrally coordinated by two N,N'-bidentate 2-(morpholin-4-yl)ethanamine ligands and two trans-located Cl atoms. In the crystal, adjacent molecules are linked by N-H center dot center dot center dot Cl and C-H center dot center dot center dot O hydrogen bonds into a three-dimensional structure. An intramolecular C-H center dot center dot center dot Cl hydrogen bond is also observed.